EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI KELAS VIII SMP NEGERI 2 BATANG ANGKOLA - Ashar Lubis (JURNAL MathEdu (Mathematic Education Journal), 2018)
This study aims to describe effectiveness of using Problem Based Learning model on students’ mathematical problem solving ability at the eighth grade students of SMP Negeri 2 Batang Angkola. The research was conducted by using experimental method with 33 students as the sample and they were taken by using cluster sampling technique from 160 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using Problem Based Learning model was 3.20 (very good category) and b) the average of students’ mathematical problem solving ability before using Problem Based Learning model was 64.61 (enough category) and after using Problem Based Learning model was 84.12 (very good category). Furthermore, based on inferential statistic by using paired sample ttest and helping SPSS version 17, the result showed the significant value was less than 0.05 (0.000<0.05). It means, there is a significant effectiveness of using Problem Based Learning model on students’ mathematical problem solving ability at the eighth grade students of SMP Negeri 2 Batang Angkola.